Eutectoid high-entropy alloy and preparation method thereof

By designing the euthanized structure of BCC+B2 structure in high-entropy alloys, the problem that existing high-entropy alloys are difficult to ensure both strength and plasticity is solved, and the coordinated improvement between strength and plasticity is achieved.

CN119592861APending Publication Date: 2025-03-11CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656689.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing high-entropy alloys are difficult to ensure both strength and plasticity.

Method used

By designing the alloy composition and adjusting the heat treatment process, an euthanized high-entropy alloy with BCC+B2 structure was prepared to form a smaller sheet structure to achieve a coordinated improvement in strength and plasticity.

Benefits of technology

The alloy exhibits good strength and plasticity matching, and fine crystal strengthening is conducive to the coordinated improvement of strength and plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592861A_ABST
    Figure CN119592861A_ABST
Patent Text Reader

Abstract

The invention discloses an eutectoid high-entropy alloy and a preparation method thereof, the eutectoid high-entropy alloy comprises the following atomic components: Co, Fe, Ni and Al, and the atomic mole percentage of Ni to Al to Co to Fe is (18-20)%: (5-7)%: (34-36)%: (39-41)%. The preparation process comprises the following steps that the raw materials (the purity is larger than or equal to 99.8 wt%) with the mole percentage are prepared and placed in a high-vacuum non-consumable electric arc smelting furnace to be smelted in a high-argon environment to form as-cast alloy, a BCC + B2 structure of an eutectoid structure is formed after heat treatment, and the prepared eutectoid high-entropy alloy has good comprehensive mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal materials and preparation thereof, and provides a eutectoid high entropy alloy and a preparation method thereof. Background Art

[0002] High entropy alloys (HEAs) are currently of great research interest in the field of materials science and engineering. Unlike traditional alloys that contain one and rarely two basic elements, HEAs contain multiple main elements, and the possible number of HEAs components is much greater than that of traditional alloys. High entropy alloys have four major effects: high entropy effect, lattice distortion effect, hysteresis diffusion effect, and cocktail effect, which give them excellent specific strength, excellent mechanical properties at high temperatures, excellent ductility and fracture toughness at low temperatures, superparamagnetism, and superconductivity. Due to their huge structural and functional potential and rich design, HEAs are promising candidates for new applications and deserve further study.

[0003] Recently, nano-lamellar structured reinforced materials with high-density interfaces have attracted special attention due to their unique mechanical and magnetic properties. In addition, this strengthening mechanism is also applicable to HEAs with nano-lamellar structures. Eutectic multi-principal alloys greatly improve the strength and ductility of cast HEAs due to the coupled deformation of lamellar phases. However, the thickness of the eutectic lamellar phase formed during solidification is usually around hundreds of nanometers, and the deformation mechanisms such as the slip system inside it are difficult to start, that is, the intermetallic compounds precipitated from the eutectic liquid phase are usually not conducive to deformation. Fortunately, in traditional alloys, solid-state phase transformation can obtain finer lamellar structures, such as pearlite formed by eutectoid reaction. If the eutectoid transformation of traditional alloys is introduced into HEAs, a finer lamellar structure can be obtained. According to the Hall-Petch effect, fine lamellar spacing is conducive to obtaining alloy materials with ultra-high strength and plasticity. The compositions of eutectoid high entropy alloys discovered at home and abroad include BCC+Ni3Al, but this kind of organization has poor plasticity. There are also compositions like BCC+NI3Ti. Due to the large difference in the crystal cell parameters between the BCC phase and the Ni3Ti phase and the Ni3Al phase, it is difficult to form a coherent or semi-coherent relationship, and it is difficult to deform in coordination, thus affecting the overall performance of the material. The BCC+B2 eutectoid high entropy alloy can solve the above problems. The BCC phase and the B2 phase have certain similarities in crystal structure. The B2 phase can be regarded as an ordered BCC structure. In the B2 phase, the atomic arrangement has a certain order, which makes it have a certain coordination with the BCC phase during the deformation process, and can achieve coordinated deformation, so that the material as a whole exhibits excellent comprehensive mechanical properties.

[0004] The research and development of eutectoid high entropy alloys (HEAs) represents a major breakthrough in the field of materials science. Through a unique multi-element alloying strategy, they break the limitations of traditional alloy design and provide new possibilities for manufacturing materials with extraordinary properties. High entropy alloys are generally composed of five or more metals or non-metals in an equiatomic or non-equiatomic ratio. Today, the development of high entropy alloys has also expanded to four or more metals or non-metal elements. Compared with traditional alloys, they exhibit excellent mechanical properties and thermal stability, especially the potential for application in high temperature environments, which is particularly important in aerospace, energy development, automobile manufacturing and other fields that require high-performance materials. Summary of the invention

[0005] In view of the problem that it is difficult for existing high entropy alloys to simultaneously ensure strength and plasticity, the present invention provides a eutectoid high entropy alloy and a preparation method thereof.

[0006] To achieve the purpose of the present invention, the following technical solutions are provided: A eutectoid high entropy alloy, wherein the raw material components are, by atomic molar percentage, 18-20% Ni, 5-7% Al, 34-36% Co, and 39-41% Fe. The alloy is a BCC+B2 structure of a nano-laminated eutectoid structure, wherein the unit cell parameter of the BCC phase is about 0.2866nm, the unit cell constant of the B2 phase ranges from 0.2856nm to 0.2952nm, the unit cell constants of the two phases are close, and the two phases have a coherent and semi-coherent orientation relationship; the relative content of the B2 phase is 9%-35%, and the average lamella thickness of the B2 phase is between 90nm and 120nm.

[0007] As a preferred embodiment, when the raw material components are as follows in atomic molar percentage: Ni: 19%, Al: 6%, Co: 35%, Fe: 40%, the unit cell parameter of the BCC phase of the alloy is about 0.2866nm, the unit cell constant of the B2 phase ranges between 0.2922nm; the average lamellar structure size of the B2 phase is 115nm.

[0008] In the technical solution of the present invention, a eutectoid high entropy alloy is successfully prepared through reasonable element selection and composition adjustment after a series of heat treatments. This alloy forms a BCC+B2 structure of eutectoid structure. Compared with eutectic high entropy alloy, this alloy has a finer lamellar structure, and fine grain strengthening is conducive to the synergistic improvement of strength and plasticity. The unit cell parameters of the BCC phase are close to the unit cell constants of the B2 phase, and they have coherent and semi-coherent orientation relationships, synergistic deformation, and show good strength and plasticity matching.

[0009] The preparation steps of this eutectoid high entropy alloy are as follows: Step (1): Place the raw materials, Al, Ni, Co, Fe in order from bottom to top, on a water-cooled copper crucible, and at the same time place pure titanium for oxygen absorption into another copper crucible; Step (2): using a non-consumable vacuum melting furnace for melting, evacuating the melting furnace twice, aligning the electrode with a copper crucible containing pure Ti, striking an arc and melting to remove residual oxygen, then moving the arc to a high entropy alloy raw material crucible for melting to obtain the cast high entropy alloy; Step (3): heat treatment, subjecting the cast alloy prepared in step (2) to heat treatment, wherein the heat treatment process includes solution treatment and annealing treatment, to obtain a eutectoid high entropy alloy.

[0010] In some embodiments, it is unavoidable to prepare the raw materials, specifically including selecting Ni, Co, Fe and Al raw materials with a purity greater than 99.8% (wt); wherein Fe and Ni are in granular form, Co and Al are in block form, mechanically removing the oxide layer, ultrasonically cleaning the selected raw materials, and fully drying; converting the mass percentage by molar percentage, and preparing the required raw materials Ni, Co, Fe and Al according to the required quality requirements.

[0011] In some embodiments, during the process of placing the raw materials, the prepared raw materials are stacked in order according to their melting points and placed on water-cooled copper, from bottom to top, namely Al, Ni, Co, and Fe, and pure titanium for oxygen absorption is placed in another copper crucible.

[0012] In some embodiments, a non-consumable vacuum melting furnace is used for melting, and the melting furnace is evacuated twice using a mechanical pump and a molecular pump. The first vacuum is evacuated to 9.0×10 -2 Pa~9.5×10 -2 Pa, and then filled with argon to -0.6×10 5 Pa~-0.5×10 5 Pa; then further evacuate the furnace with a molecular pump to a pressure of 9.0×10 -3 ~9.5×10 -3 Pa, and then filled with argon to -0.6×10 5 Pa~-0.5×10 5 MPa.

[0013] In some preferred cases, the first vacuum is evacuated to 9.5×10 -2 Pa, and then filled with argon to -0.5×10 5 Pa, and further evacuate the furnace with a molecular pump to a pressure of 9.5×10 -3 Pa, and then filled with argon to -0.5×10 5 MPa.

[0014] In some embodiments, the electrode is aligned with a crucible filled with pure Ti, and the electrode is about 3-5 mm away from the pure Ti. After the arc is struck, the melting is performed for 2-3 min to remove residual oxygen, and then the arc is moved to the high entropy alloy raw material crucible for melting.

[0015] During the smelting process, the arc current intensity is increased from 10-20A to 50-70A slowly, and smelted for 35-50s, then the current is increased to 120-160A, smelted for 1-2 min, and then the current is increased to 300-330A again, smelted for 3-4min, and finally the current is increased to 360-380A for 2-3min.

[0016] In some preferred cases, the current is controlled from 20A, and the current is slowly increased to 50A, and the melting is performed for 50s, and then the current is increased to 160A, and the melting is performed for 2 minutes, and the current is increased to 330A again, and the melting is performed for 4 minutes, and finally the current is increased to 360A and the melting is performed for 3 minutes. After each melting, the alloy ingot is turned over and remelted by a robot, and this operation is repeated 6 times to obtain the cast high entropy alloy.

[0017] Step (4): heat treatment, the cast alloy prepared in step (3) is heat treated, the heat treatment process is solution treatment and annealing treatment, the solution treatment temperature is 1100-1200°C, the solution treatment time is 9.5-10.5h, the solution treatment heating rate is 6-8°C / min, the annealing temperature is 525-625°C and the annealing time is 7.5-8.5h, the annealing heating rate is 3-4°C / min, the solution treatment and annealing treatment are both performed in a box-type heat treatment furnace and cooled by water cooling to obtain a nano-layered eutectoid high entropy alloy.

[0018] The present invention has the following innovations and advantages: The present invention introduces the eutectoid transformation of traditional alloys into high entropy alloys by designing alloy composition and adjusting heat treatment process parameters, thereby obtaining a microstructure with a finer lamellar structure, and fine grain strengthening is beneficial to the synergistic improvement of strength and plasticity.

[0019] The present invention obtains a BCC+B2 structure of a eutectoid structure, which has excellent strength and plasticity. The BCC phase and the B2 phase have certain similarities in crystal structure, and the two can be deformed in coordination. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The experimental flow chart of the present invention.

[0021] Figure 2 XRD patterns of eutectoid high entropy alloys at four different annealing temperatures.

[0022] Figure 3Figures (a~d) correspond to scanning electron microscope images of comparative example 2, embodiment 2, embodiment 1, and comparative example 1, respectively.

[0023] Figure 4 This is the scanning electron microscope image of Comparative Example 3.

[0024] Figure 5 This is the metallographic microscope phase image of Comparative Example 4.

[0025] Figure 6 Room temperature compressive engineering stress-strain curves of eutectoid high entropy alloys at four different annealing temperatures. DETAILED DESCRIPTION

[0026] In the present invention, various raw materials, reagents, instruments and equipment involved can be obtained through conventional channels.

[0027] In the present invention, for phase analysis, a cylindrical alloy sample of Φ5 mm × 6 mm is cut from the ingot by electric spark wire cutting technology, and an Ultima IV type Cu Kα ray diffractometer (λ=1.54Å) is used for X-ray diffraction analysis, with an operating voltage of 40 Kv, an operating current of 40 mA, a 2θ scanning range of 20°~100°, and a scanning speed of 4° / min.

[0028] In the present invention, for microstructure observation, a scanning electron microscope is used to observe the structure of the sample at different magnifications. In the present invention, in addition to the test of mechanical properties, a room temperature compression experiment is carried out. The national metal material room temperature compression standard (GB / T 7314-2017) is adopted. A Φ3mm×6mm cylindrical alloy sample is cut from the ingot by electric spark wire cutting technology. The experimental compression loading rate is 0.36mm / min. Three experiments are carried out for each component alloy to take the average value to ensure the rationality of the stress-strain curve.

[0029] In the present invention, all operation processes are performed in accordance with the experimental requirements, and all professional terms used in the related professions have the same meanings as those generally understood by those skilled in the art.

[0030] The following are specific implementation cases to further illustrate the present invention.

[0031] Example 1 A eutectoid high entropy alloy Fe 40 Co 35 Ni 19 The preparation method of Al6 is as follows: Step 1: Select metal raw materials of Co, Al, Fe and Ni, and the purity of all metal raw materials is greater than 99.8wt.%. Fe and Ni are in granular form, and Co and Al are in block form. Mechanically remove the oxide layer, ultrasonically clean the selected raw materials, and fully dry them; Step 2: The atomic molar percentages of the alloy are Ni: 19%, Al: 6%, Co: 35%, and Fe: 40%. The mass percentages are converted based on the molar percentages, and the required raw materials Ni, Co, Fe, and Al are prepared according to the required mass using an electronic scale.

[0032] Step 3: Before placing the raw materials in the smelting furnace, wipe the water-cooled copper crucible with alcohol cotton until it is clean, and stack the prepared raw materials in order of melting point on the water-cooled copper, from bottom to top: Al, Ni, Co, Fe, and at the same time, put pure titanium for oxygen absorption into another copper crucible; Step 4: Use a non-consumable vacuum melting furnace for melting, and use a mechanical pump and a molecular pump to evacuate the melting furnace twice. The first vacuum is to 9.5×10 -2 Pa, and then filled with argon to -0.5×10 5 Pa, and further evacuate the furnace with a molecular pump to a pressure of 9.5×10 -3 Pa, and then filled with argon to -0.5×10 5 MPa, aim the electrode at the crucible filled with pure Ti, and the electrode is about 3-5 mm away from the pure Ti, melt for 2-3 min after arcing, remove residual oxygen, and then move the arc to the high entropy alloy raw material crucible, control the current from 20A, slowly increase the current to 50A, melt for 50s, then increase the current to 160A, melt for 2 min, increase the current to 330A again, melt for 4min, and finally increase the current to 360A and melt for 3min. After each melting, use a robot to turn the alloy ingot over and remelt it. Repeat this operation 6 times to obtain the cast high entropy alloy.

[0033] Step 5, heat treatment, the cast alloy prepared in step 4 is heat treated, the heat treatment process adopts solid solution treatment 1150℃+10h and annealing treatment 600℃+8h, the solid solution treatment heating rate is 6℃ / min, the annealing treatment heating rate is 4℃ / min, the homogenization annealing treatment and annealing treatment are both cooled by a box-type heat treatment furnace and water cooling to obtain a eutectoid high entropy alloy.

[0034] Example 2 A method for preparing a eutectoid high entropy alloy Fe40Co35Ni19Al6 is as follows: Only the annealing temperature was changed to 550°C, and the remaining steps were the same as in Example 1.

[0035] Comparative Example 1 A method for preparing a eutectoid high entropy alloy Fe40Co35Ni19Al6 is as follows: Only the annealing temperature was changed to 650°C, and the remaining steps were the same as in Example 1.

[0036] Comparative Example 2 A method for preparing a high entropy alloy Fe40Co35Ni19Al6 is as follows: Only the annealing temperature was changed to 500°C, and the remaining steps were the same as those in Example 1.

[0037] Comparative Example 3 A high entropy alloy Fe 55 Co 20 Ni 15 Al 10 The preparation method is as follows: Step 1: Select metal raw materials of Co, Al, Fe and Ni, and the purity of all metal raw materials is greater than 99.8wt.%. Fe and Ni are in granular form, and Co and Al are in block form. Mechanically remove the oxide layer, ultrasonically clean the selected raw materials, and fully dry them; Step 2: The atomic molar percentages of the alloy are Ni: 15%, Al: 10%, Co: 20%, and Fe: 55%. The mass percentages are converted based on the molar percentages, and the required raw materials Ni, Co, Fe, and Al are prepared according to the required mass using an electronic scale.

[0038] Step 3: Before placing the raw materials in the smelting furnace, wipe the water-cooled copper crucible with alcohol cotton until it is clean, and stack the prepared raw materials in order of melting point on the water-cooled copper, from bottom to top: Al, Ni, Co, Fe, and at the same time, put pure titanium for oxygen absorption into another copper crucible; Step 4: Use a non-consumable vacuum melting furnace for melting, and use a mechanical pump and a molecular pump to evacuate the melting furnace twice. The first vacuum is to 9.5×10 -2 Pa, and then filled with argon to -0.5×10 5 Pa, and further evacuate the furnace with a molecular pump to a pressure of 9.5×10 -3 Pa, and then filled with argon to -0.5×10 5 MPa, aim the electrode at the crucible filled with pure Ti, and the electrode is about 3-5 mm away from the pure Ti, melt for 2-3 min after arcing, remove residual oxygen, and then move the arc to the high entropy alloy raw material crucible, control the current from 20A, slowly increase the current to 50A, melt for 50s, then increase the current to 160A, melt for 2 min, increase the current to 330A again, melt for 4min, and finally increase the current to 360A and melt for 3min. After each melting, use a robot to turn the alloy ingot over and remelt it. Repeat this operation 6 times to obtain the cast high entropy alloy.

[0039] Step 5: heat treatment. The cast alloy prepared in step 4 is heat treated. The heat treatment process adopts annealing at 600°C+2h. The annealing heating rate is 4°C / min. The annealing is carried out in a box-type heat treatment furnace and water cooling to obtain a BCC+B2 phase high entropy alloy.

[0040] Comparative Example 4 A method for preparing a high entropy alloy Fe40Co35Ni19Al6 is as follows: Only the heat treatment process was changed, the solution treatment temperature was 1100°C, the solution treatment time was 4 h, the heat treatment temperature was 550°C, the heat treatment time was 2 h, and the remaining steps were the same as in Example 1 to obtain an FCC+B2 phase high entropy alloy.

[0041] like Figure 2 , It can be seen from the X-ray diffractometer analysis that Examples 1, 2 and Comparative Examples 1, 2 are all formed by BCC phase and B2 (NiAl) phase.

[0042] like Figure 3 Figures (a~d) correspond to comparative example 2, example 2, example 1, and comparative example 1, respectively. Combining scanning electron microscopy and X-ray diffraction analysis, it can be seen that the four examples all present a BCC+B2 structure of the eutectoid structure. Figure 4 e) Corresponding to proportion 3, the B2 phase precipitated directly from the liquid phase was obtained. Although it is also a BCC+B2 structure, the B2 phase is a coarse structure. Figure 5 The metallographic microscope phase image corresponding to Example 4 is FCC+B2 phase structure.

[0043] The following table compares the yield strength, fracture strength and fracture strain of Examples 1-2 and Comparative Examples 1-2.

[0044]

[0045] Table 1 like Figure 6 As shown in Table 1, it can be seen that the strength and plasticity of 550°C and 600°C within 525°C-625°C are more excellent, the plasticity of Comparative Example 1 is good but the yield strength is too low, and the strength performance of Comparative Example 2 is superior but the plasticity is poor. In addition, the yield strength of Comparative Example 3 is high but the plasticity is poor, and the plasticity of Comparative Example 4 is good but the strength is poor.

[0046] Table 2

[0047] The B2 phase layers of Examples 1 and 2 are finer than those of Comparative Example 1, and the B2 phase content is higher than that of Comparative Example 2. The B2 phase of Comparative Example 3 is too large in size, reaching the micron level, and the B2 phase is directly precipitated from the liquid phase and has no coherence relationship with the BCC phase.

[0048] Comparative Example 4 is a FCC phase + B2 phase of a martensitic structure, and the BCC + B2 phase cannot be achieved. Its yield strength is lower than that of BCC + B2, and the unit cell constant of the FCC phase is about 0.405nm. Compared with the BCC phase, the unit cell constant of the B2 phase is closer to the BCC phase.

[0049] The present invention successfully prepares a eutectoid high entropy alloy through reasonable element selection and composition adjustment after a series of heat treatments. This alloy forms a BCC+B2 structure of eutectoid structure. Compared with eutectic high entropy alloy, this alloy has a finer lamellar structure, and fine grain strengthening is conducive to the synergistic improvement of strength and plasticity. The unit cell parameters of the BCC phase are close to the unit cell constants of the B2 phase, and they have coherent and semi-coherent orientation relationships, synergistic deformation, and show good strength and plasticity matching.

[0050] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, further improvements on the experimental method of the present invention, or making some simple deductions or substitutions, all of which should be regarded as falling within the protection scope of the present invention.

Claims

1. A eutectoid high entropy alloy, characterized in that: The raw material components are as follows in atomic molar percentage: Ni: 18~20%, Al: 5~7%, Co: 34~36%, Fe: 39~41%. The alloy has a BCC+B2 structure of nano-laminated eutectoid structure, wherein the unit cell parameter of the BCC phase is approximately 0.2866nm, and the unit cell constant of the B2 phase ranges from 0.2856nm to 0.2952nm. The unit cell constants of the two are close, and have coherent and semi-coherent orientation relationships; the relative content of the B2 phase is 9%~35%, and the average lamella thickness of the B2 phase is between 90nm and 120nm.

2. The eutectoid high entropy alloy according to claim 1, characterized in that When the raw material components are as follows in atomic molar percentage: Ni: 19%, Al: 6%, Co: 35%, Fe: 40%, the unit cell parameter of the BCC phase is approximately 0.2866nm, the unit cell constant of the B2 phase is in the range of 0.2922nm, with coherent and semi-coherent orientation relationships, the relative content of the B2 phase is 32%, and the average lamella thickness of the B2 phase is 115nm.

3. The method for preparing a eutectoid high entropy alloy according to claim 1 or 2, characterized in that: The alloy preparation steps are as follows: Step (1): Place the raw materials, Al, Ni, Co, Fe in order from bottom to top, on a water-cooled copper crucible, and at the same time place pure titanium for oxygen absorption into another copper crucible; Step (2): using a non-consumable vacuum melting furnace for melting, using a mechanical pump and a molecular pump to evacuate the melting furnace twice, then aligning the electrode with a copper crucible containing pure Ti, striking an arc and melting to remove residual oxygen, then moving the arc to a high entropy alloy raw material crucible for melting to obtain the cast high entropy alloy; Step (3): heat treatment, subjecting the cast alloy prepared in step (2) to heat treatment, wherein the heat treatment process includes solution treatment and annealing treatment, to obtain a eutectoid high entropy alloy.

4. The method for preparing a eutectoid high entropy alloy according to claim 3, characterized in that: In step (2), the vacuum is first drawn to 9.0 × 10 -2 Pa~9.5×10 -2 Pa, and then filled with argon to -0.6×10 5 Pa~-0.5×10 5 Pa; then further evacuate the furnace with a molecular pump to a pressure of 9.0×10 -3 ~9.5×10 -3 Pa, and then filled with argon to -0.6×10 5 Pa~-0.5×10 5 MPa.

5. The method for preparing a eutectoid high entropy alloy according to claim 4, characterized in that: During the smelting process in step (2), the arc current intensity is increased from 10-20A to 50-70A slowly, and the smelting is carried out for 35-50s. Then the current is increased to 120-160A and the smelting is carried out for 1-2 min. The current is increased to 300-330A again and the smelting is carried out for 3-4 min. Finally, the current is increased to 360-380A and the smelting is carried out for 2-3 min.

6. The method for preparing a eutectoid high entropy alloy according to claim 3, characterized in that: During the solution treatment process in step (3), the temperature is raised to 1100-1200°C at a heating rate of 6-8°C / min, the solution treatment is carried out for 9.5-10.5h, and then a water cooling treatment is carried out.

7. The method for preparing a eutectoid high entropy alloy according to claim 6, characterized in that: During the annealing treatment in step (3), the temperature is raised to 525-625°C at a heating rate of 3-4°C / min, and the heat treatment is performed for 7.5-8.5h, followed by water cooling.